Fungus gnats (Diptera: Sciaridae) damage the desert rose (Adenium obesum Forssk. Roem. & Schult) crop in Jataí – Goiás, Brazil - Somera, Andreia; Gomes, Francielly Rodrigues [UNESP]; Ragagnin, Angelita Lorrayne Soares Lima; Silveira-Neto, Américo Nunes; Hurtado-Salazar, Alejandro; Cruz, Simério Carlos da Silva; da Silva, Danielle Fabíola Pereira; Rodrigues, Claudia Dayane Marques; Kuster, Vinícius Coelho (FapUNIFESP (SciELO), 2024)
Recent rise in desert rose production, the expanded cultivation of this species may promote infestation by certain insects and mites. One such insect, the fungus gnats (Bradysia sp), also known as fungus flies, have been damaging numerous ornamental plant species. This study reported the incidence of fungus gnats infesting desert rose plants in the municipality of Jataí-GO, Brazil. Throughout 2022, we evaluated 48 desert rose plants for parasitic occurrences through direct observation. Sticky traps were used to record adult insects. Damage to plant organs has been documented and the presence of parasites at various stages of development with digital photographs. The incidence of fungal gnats is confirmed by observing adult insects and larvae in the plant substrate and roots. Of the 48 plants evaluated, 39 showed signs of infestation. Symptoms of a fungus gnat attack on desert rose include small necrotic lesions on new roots, progressive root rot, and a withered caudex resembling dehydration. The fungus gnats attack can cause the desert rose caudex to wilt, reducing its size and losing part of its shape, fact that can compromise the commercialization of this crop.
Fungus gnats (Diptera: Sciaridae) causam danos na cultura da rosa do deserto (Adenium obesum Forssk. Roem. & Schult) em Jataí – Goiás, Brasil
Keywords: Bradysia sp; fungus fly; ornamental plants